Revisiting the Cupidito unit (Cupido Formation) along peritidal carbonates from northeastern Mexico - Felipe de Jesús Torres de la Cruz; Elizabeth Chacón-Baca; Gabriel Chávez-Cabello; María Isabel Hernández-Ocaña (Revista Mexicana de Ciencias Geológicas)
Depositional episodes are readily identified along representative localities of the Lower Cretaceous Cupido platform in northeastern Mexico. The basal part of the Cupido Formation exhibits a progradational reef platform that, at the upper limit, is truncated by a sequence boundary defined by a breccia. This breccia marks the development of a peculiar sedimentary facies informally known as the Cupidito unit, a distinctive stratigraphical unit in northeastern Mexico that remained uninterpreted for decades. Through the analysis of facies, microfacies and stable isotope comparisons from representative localities (Potrero Chico, Potrero de García, La Huasteca, La Muralla and Puerto Mexico) and from other previously reported outcrops, this work describes six diagnostic features for Cupidito and an improved stratigraphic model is proposed. The depositional sequence suggests a broad flat-topped platform with a general low organic productivity and restricted conditions followed by recurrent inundations of lagoon waters. Before drowning, this carbonate platform remained under equilibrium conditions interrupted by short pulses of relative higher-temperatures (48.3 °C and 39.2 °C). Coral-rudist-stromatoporoid patch-reefs with inferred inter-tropical temperatures between 31.5 °C and 32.2 °C originated as a progradational response to the instauration of a new Sequence Boundary at the base of Cupidito.